Advances in the therapy of small cell lung cancer - Vrána, D (Klinicka onkologie, 2021)
Small cell lung cancer represents a disease with poor prognosis. Despite rapid progress in the fields of medical or radiation oncology, the treatment strategy of the small cell lung cancer has remained almost unchanged for over the last 30 years. Prophylactic cranial irradiation and irradiation of the primary lung tumor according to CREST clinical trial improved the median overall survival in months. Until the launch on immunotherapy, the systemic treatment didnt make significant progress, unfortunately including targeted therapy. Immunotherapy significantly changed the treatment outcomes of the several tumor types and finally even the prognosis of small cell lung cancer. Clinical trials with atezolizumab and durvalumab have further moved forward the median overall survival by more than 2 months without significant increase in the treatment toxicity and worsening of the patients quality of life. In the combination with chemotherapy, atezolizumab and durvalumab represents a new gold standard in the treatment of small cell lung cancer.
Keywords: Chemotherapy; nádory plic; malobuněčný karcinom plic; kombinovaná terapie; lung cancer; Lung Neoplasms; immunotherapy; Humans; Combined Modality Therapy; Small Cell Lung Carcinoma; immunotherapy; lidé; chemotherapy